Bleaching gel mixed with MI Paste Plus reduces penetration of H2O2 and damage to pulp tissue and maintains bleaching effectiveness - Barbosa, Jéssica Galbiati [UNESP]; Benetti, Francine [UNESP]; de Oliveira Gallinari, Marjorie [UNESP]; Carminatti, Marina [UNESP]; da Silva, Anna Beatriz Dias [UNESP]; Lopes, Isabela Nakahara Ikeda [UNESP]; Briso, André Luiz Fraga [UNESP]; Cintra, Luciano Tavares Angelo [UNESP] (Springer Nature, 2019)
Objectives: MI Paste Plus remineralizer (Rem) strengthens dental structures after bleaching. We investigated the effect of Rem on the penetration of hydrogen peroxide (H2O2), bleaching effectiveness, and pulp inflammation after bleaching. Materials and methods: Bovine disks were grouped as follows (n = 10): control (untreated), bleached (Ble; 35% H2O2, 30 min), Ble-Rem (H2O2 followed by Rem, 30 min), Rem-Ble (Rem followed by H2O2), Rem-Ble-Rem (Rem before and after H2O2), and Ble+Rem (mixture of Rem with H2O2, 1:1, 30 min). The penetration of H2O2 was quantified and bleaching efficacy was analyzed. Upper rat molars (n = 10) received the same treatments at random. The rats were euthanized after two days and 30 days, and their jaws were removed for histological analysis. Statistical tests were performed (P < 0.05). Results: The bleached groups, except Ble+Rem (P > 0.05), showed significant H2O2 penetration compared with control (P < 0.05). Color alteration analysis showed that ΔL and ΔE were significantly higher in the bleached groups than those in control (P < 0.05); the Δb of the bleached groups differed from that of control at 24 h (P < 0.05). At two days, necrosis or inflammation was observed in the bleached groups compared with control (P < 0.05), except Ble+Rem, which was similar to control (P > 0.05). At 30 days, tertiary dentin formation was significant in the bleached groups (P < 0.05), except Ble+Rem (P > 0.05). Conclusion: The mixture of MI Paste Plus and bleaching gel reduces H2O2 penetration and pulp damage and maintains bleaching effectiveness. Clinical relevance: Because bleaching can damage dental tissues, we studied a new bleaching protocol that reduces damage to the pulp tissue while maintaining bleaching efficiency: a single application of 30 min of MI Paste Plus mixed with 35% H2O2 bleaching gel (1:1).
Keywords: Casein phosphopeptide-amorphous calcium phosphate (CPP-ACP); Dental bleaching; Hydrogen peroxide; MI Paste Plus; Pulp inflammation